ETHNOMATHEMATICAL EXPLORATION OF THE ENGKLEK GAME IN ELEMENTARY MATHEMATICS LEARNING - Rahmawati Aulia Yuliani; Dian Anggraeni Maharbid (Universitas Muhammadiyah Metro, 2026)
Mathematics learning in elementary schools is often perceived as abstract and less engaging for students, which can hinder their understanding of mathematical concepts. Integrating cultural elements into learning activities can help create more meaningful and contextual learning experiences. One approach is through ethnomathematics embedded in traditional games such as engklek. Therefore, this study aims to explore the ethnomathematical values in the traditional engklek game and examine its potential as a medium for teaching mathematics in elementary schools. This study employed a qualitative ethnographic approach. The research subjects consisted of elementary school teachers, students, and cultural experts selected through purposive sampling. Data were collected through interviews, observations, and documentation. The data were analyzed using qualitative analysis techniques, including data reduction, data display, and conclusion drawing. The results show that the traditional engklek game contains various mathematical concepts, including geometry, numbers, and measurement. These concepts can be observed in the patterns of the game field. The findings also indicate that using engklek as a learning medium can create contextual and engaging learning experiences, enhance students’ critical thinking skills, and promote collaboration and character values. Therefore, integrating ethnomathematics through traditional games can support meaningful and culturally relevant mathematics learning in elementary schools Pembelajaran matematika di sekolah dasar seringkali dianggap abstrak dan kurang menarik bagi siswa, yang dapat menghambat pemahaman mereka terhadap konsep matematika. Mengintegrasikan unsur budaya ke dalam kegiatan pembelajaran dapat membantu menciptakan pengalaman belajar yang lebih bermakna dan kontekstual. Salah satu pendekatannya adalah melalui etnomatematika yang tertanam dalam permainan tradisional seperti engklek. Oleh karena itu, penelitian ini bertujuan untuk mengeksplorasi nilai-nilai etnomatematika dalam permainan tradisional engklek dan menguji potensinya sebagai media pengajaran matematika di sekolah dasar. Penelitian ini menggunakan pendekatan etnografi kualitatif. Subjek penelitian terdiri dari guru sekolah dasar, siswa, dan pakar budaya yang dipilih melalui pengambilan sampel bertujuan. Data dikumpulkan melalui wawancara, observasi, dan dokumentasi. Data dianalisis menggunakan teknik analisis kualitatif, termasuk reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa permainan tradisional engklek mengandung berbagai konsep matematika, termasuk geometri, angka, dan pengukuran. Konsep-konsep ini dapat diamati dalam pola lapangan permainan. Temuan juga menunjukkan bahwa penggunaan engklek sebagai media pembelajaran dapat menciptakan pengalaman belajar yang kontekstual dan menarik, meningkatkan kemampuan berpikir kritis siswa, dan mendorong kolaborasi serta nilai-nilai karakter. Oleh karena itu, mengintegrasikan etnomatematika melalui permainan tradisional dapat mendukung pembelajaran matematika yang bermakna dan relevan secara budaya di sekolah dasar.